Two related but distinct chondroitin sulfate mimetope octasaccharide sequences recognized by monoclonal antibody WF6 - Peraphan Pothacharoen (2018)
Chondroitin sulfate (CS) proteoglycans are major components of cartilage and other connective tissues. The monoclonal antibody WF6, developed against embryonic shark cartilage CS, recognizes an epitope in CS chains, which is expressed in ovarian cancer and variably in joint diseases. To elucidate the structure of the epitope, we isolated oligosaccharide fractions from a partial chondroitinase ABC digest of shark cartilage CS-C and established their chain length, disaccharide composition, sulfate content, and sulfation pattern. These structurally defined oligosaccharide fractions were characterized for binding to WF6 by enzyme-linked immunosorbent assay using an oligosaccharide microarray prepared with CS oligosaccharides derivatized with a fluorescent aminolipid. The lowest molecular weight fraction recognized by WF6 contained octasaccharides, which were split into five subfractions. The most reactive subfraction contained several distinct octasaccharide sequences. Two octasaccharides, ΔD-C-C-C and ΔC-C-A-D (where A represents GlcUAβ1-3GalNAc(4-O-sulfate), C is GlcUAβ1-3Gal-NAc(6-O-sulfate), D is GlcUA(2-O-sulfate)β1-3GalNAc(6- Osulfate), ΔC is Δ4,5HexUAα1-3GalNAc(6-O-sulfate), and ΔD is Δ4,5HexUA(2-O-sulfate)α1-3GalNAc(6-O-sulfate)), were recognized by WF6, but other related octasaccharides, ΔC-A-D-C and ΔC-C-C-C, were not. The structure and sequences of both the binding and nonbinding octasaccharides were compared by computer modeling, which revealed a remarkable similarity between the shape and distribution of the electrostatic potential in the two different octasaccharide sequences that bound to WF6 and that differed from the nonbinding octasaccharides. The strong similarity in structure predicted for the two binding CS octasaccharides (ΔD-C-C-C and ΔC-C-A-D) provided a possible explanation for their similar affinity for WF6, although they differed in sequence and thus form two specific mimetopes for the antibody. © 2007 by The American Society for Biochemistry and Molecular Biology, Inc.